1991
DOI: 10.1073/pnas.88.18.8048
|View full text |Cite
|
Sign up to set email alerts
|

Direction of transneuronal transport of herpes simplex virus 1 in the primate motor system is strain-dependent.

Abstract: We ex the axonal transport of two strain of herpes simplex virus 1 (HSV-1) within the central nervous system ofcebus monkeys. Each strain was inijected into the "arm area" of the primry motor cortex. One strain, HSV-1(McIntyre-B), was transported transneuronaly in the retrograde direction. It infected neurons at sites known to project to the arm area of the primary motor cortex (e.g., ventrolateral thalamus). In addition-, "second-order" neurons were labeled in the deep cerebellar nuclei (dentate and interposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
136
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(145 citation statements)
references
References 39 publications
8
136
1
Order By: Relevance
“…For example, in the present study using H129, we found infection in the ipsilateral DRG beginning at 48 h postinjection, as well as in the ipsilateral T13 sympathetic ganglion. H129 is most useful because of its strictly anterograde travel through neural circuits (6,43,50). The labeling of T13 postganglionic SNS cells may have occurred because they also are first-order neurons, and H129 initially infects all first-order neurons, as was shown with stomach injections of H129 (33).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…For example, in the present study using H129, we found infection in the ipsilateral DRG beginning at 48 h postinjection, as well as in the ipsilateral T13 sympathetic ganglion. H129 is most useful because of its strictly anterograde travel through neural circuits (6,43,50). The labeling of T13 postganglionic SNS cells may have occurred because they also are first-order neurons, and H129 initially infects all first-order neurons, as was shown with stomach injections of H129 (33).…”
Section: Discussionmentioning
confidence: 89%
“…The labeling of T13 postganglionic SNS cells may have occurred because they also are first-order neurons, and H129 initially infects all first-order neurons, as was shown with stomach injections of H129 (33). Further progression into the CNS via the WAT SNS circuits would require retrograde spread of the virus across synapses, which the H129 is not capable of doing (17,33,50). In addition, the labeling of the Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the cerebellar activity may reflect the brisk termination of the fingertip force increase, which is triggered by tactile afferents in the fingertips and occurs Ïł100 ms after the premature liftoff (Westling and Johansson, 1987). The cerebellum has inhibitory outputs to several different cortical and subcortical regions, including thalamocortical projections to the primary motor cortex (Zemanick et al, 1991;Kelly and Strick, 2003), that could mediate the seen motor response. The thalamocortical projections to the motor cortex receive input from lobule VI of the cerebellum (Kelly and Strick, 2003), which is the same region where the peak of the activity was located in the present study (i.e., lobule VI at the border zone between the medial and lateral cerebellum; x Ï­ Ï©15).…”
Section: Corrective Responses and Their Neural Correlatesmentioning
confidence: 99%
“…The H129 strain of herpes simplex virus-1 (Dix et al, 1983) undergoes anterograde transneuronal transport in cebus monkeys after inoculation of primary motor cortex (Zemanick et al, 1991;Kelly and Strick, 2003) and in mice after inoculation of tooth pulp (Barnett et al, 1995) or the vitreous body of the eye (Sun et al, 1996). The present report documents our new finding that strain H129 also has utility as an anterograde transneuronal viral tracer in rats, effectively revealing CNS neurons that receive direct and relayed viscerosensory input from the stomach wall.…”
Section: Introductionmentioning
confidence: 99%